Materialistic Value and Credit Card Usage as Predictors of Compulsive Clothing Buying among Young Adult Women - Sari, Meylisa Permata; Suyasa, P. Tommy Y. S. (Makara Human Behavior Studies in Asia, 2017)
This study aimed to determine the role of the centrality/success and happiness dimensions of materialistic value, and credit card usage to predict compulsive clothing buying behavior of young adult women, and to determine which factor can be a better predictor. Multiple regression analysis was conducted utilising IBM SPSS 21 to analyse the statistics. In all, 154 young adult women participated in this study. This research finds that centrality/success dimension, happiness dimension, and credit card usage can predict compulsive clothing buying among young women. Furthermore, the results also show that the dimension of materialistic value is a better predictor of compulsive clothing buying behavior compared to credit card usage. Further implications, limitations, discussion, and future research directions are discussed in the paper.